RIPK1 and RIPK3 are positive prognosticators for cervical cancer patients and C2 ceramide can inhibit tumor cell proliferation in vitro - Vogelsang, Tilman L. R.; Kast, Verena; Bagnjuk, Konstantin; Eubler, Katja; Jeevanandan, Sree Priyanka; Schmoeckel, Elisa; Trebo, Anna; Topalov, Nicole Elisabeth; Mahner, Sven; Mayr, Doris; Mayerhofer, Artur; Jeschke, Udo; et al. (Frontiers in Oncology, 2023)
Necroptosis is a caspase-independent form of programmed cell death. RIPK1, RIPK3, and pMLKL are key factors in the signaling cascade of necroptosis. High-risk human papillomavirus inhibits necroptosis most likely via downregulation of RIPK3. This might enhance persistent infection with high-risk human papillomavirus which plays an important role in tumorigenesis of cervical cancer. In this study, we analyzed the expression of RIPK1, RIPK3, and pMLKL in patient-derived cervical cancer tissue and evaluated its prognostic value on overall survival, progression-free survival, and additional clinical parameters. Expression of RIPK1, RIPK3, and pMLKL was evaluated via immunohistochemistry in tissue microarrays of n = 250 patients diagnosed with cervical cancer. Since C2 ceramide is a biologically active short-chain ceramide that induces necroptosis in human luteal granulosa cells, the effect of C2 ceramide on several cervical cancer cell lines (CaSki, HeLa, SiHa) was examined. Cervical cancer patients expressing nuclear RIPK1 or RIPK3 alone or simultaneously (RIPK1 and RIPK3) had significantly longer overall survival and progression-free survival rates. C2 ceramide stimulation of cervical cancer cells led to a significant reduction of cell viability and proliferation. Simultaneous stimulation of C2 ceramide and the pan-caspase inhibitor Z-VAD-fmk, or the RIPK1-inhibitor necrostatin-1, partly reversed the negative effect of C2 ceramide on cell viability. This implies that caspase-dependent and -independent forms of cell death, including necroptosis, occur. Furthermore, in CaSki and HeLa cells live cell imaging showed morphological changes characteristic of necroptosis after stimulation with C2 ceramide. In conclusion, both RIPK1, RIPK3, and co-expression are independent positive predictors for overall survival and progression-free survival in cervical cancer patients. C2 ceramide reduced cell viability and proliferation in cervical cancer cells by inducing most likely both apoptosis and necroptosis.